Advances on P2P, Parallel, Grid, Cloud and Internet Computing Proceedings of the 11th International Conference on P2P, Parallel, Grid, Cloud and Internet Computing (3PGCIC-2016) November 5-7, 2016, Soonchunhyang University, Asan, Korea - Xhafa, Fatos; Barolli, Leonard; Amato, Flora; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
P2P, Grid, Cloud and Internet computing technologies have been very fast established as breakthrough paradigms for solving complex problems by enabling aggregation and sharing of an increasing variety of distributed computational resources at large scale. The aim of this volume is to provide latest research findings, innovative research results, methods and development techniques from both theoretical and practical perspectives related to P2P, Grid, Cloud and Internet computing as well as to reveal synergies among such large scale computing paradigms. This proceedings volume presents the results of the 11th International Conference on P2P, Parallel, Grid, Cloud And Internet Computing (3PGCIC-2016), held November 5-7, 2016, at Soonchunhyang University, Asan, Korea.
From the Content -- A Configurable Shared Scratchpad Memory for GPU-like Processors -- Research of Double Threshold Collaborative Spectrum Sensing Based on OFDM -- Research on Particle Swarm Optimization of Variable Parameter -- An Access Control Architecture for Protecting Health Information Systems.
Keywords: Telecommunication; Computational intelligence; Artificial intelligence; Communications Engineering, Networks; Computational Intelligence; Artificial Intelligence